CISSP official (ISC)² practice tests - Chapple, Mike; Seidl, David (Sybex, A Wiley Brand, 2018)
Full-length practice tests covering all CISSP domains for the ultimate exam prep The (ISC)2 CISSP Official Practice Tests is a major resource for CISSP candidates, providing 1300 unique practice questions. The first part of the book provides 100 questions per domain. You also have access to four unique 125-question practice exams to help you master the material. As the only official practice tests endorsed by (ISC)2, this book gives you the advantage of full and complete preparation. These practice tests align with the 2018 version of the exam to ensure up-to-date preparation, and are designed to cover what you'll see on exam day. Coverage includes: Security and Risk Management, Asset Security, Security Architecture and Engineering, Communication and Network Security, Identity and Access Management (IAM), Security Assessment and Testing, Security Operations, and Software Development Security. The CISSP credential signifies a body of knowledge and a set of guaranteed skills that put you in demand in the marketplace. This book is your ticket to achieving this prestigious certification, by helping you test what you know against what you need to know. Test your knowledge of the 2018 exam domains Identify areas in need of further study Gauge your progress throughout your exam preparation The CISSP exam is refreshed every few years to ensure that candidates are up-to-date on the latest security topics and trends. Currently-aligned preparation resources are critical, and periodic practice tests are one of the best ways to truly measure your level of understanding